Pengaruh Pengalaman Kerja, Tingkat Pendidikan, Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Perusahaan Wuryani Konveksi di Kota Grobogan - Widyakto, Adhi; Syafitri, Laela Deasy; niati, asih; Ariefiantoro, Teguh (Faculty of Economics and Business | Universitas Diponegoro, 2023)
This study aims to examine and analyze the effect of work experience, education level, and work discipline on employee performance at the Wuryani Convection company in Grobogan City.The population in this study were 30 employees of Wuryani Convection in Grobogan City. The instrument used in this study was in the form of a questionnaire, by testing it using multiple linear regression analysis. Data analysis methods in this study include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis t test, and coefficient of determination.The results of this study indicate that work experience has a positive but not significant effect on employee performance. The level of education has a positive and significant effect on employee performance. And work discipline has a positive and significant effect on employee performance